Hacia un sistema contractual <<uniforme>>: Modelos comparados (2005)
The construction of common judicial frames aimed to obtain harmony, integration and uniformity in private law, more specifically in the judicial regime of contracts and obligations, has forced different research groups to dedicate themselves more in the search of the common core of the contractual institution in order to consolidate a “private global right “as a first great effort which would guarantee the safety of transnational operators and the legality of commercial transactions. One of the most recent proposals is found in the rough project of the European Code of Contracts (CEC) of the academy of European Iusprivatistas in Pavia.